Second Five Year Plan Madras State A Review (Statements I, II and III) - Planning Commission (Planning Commission, 1962)
Summary Statement of Progress of Expenditure For 1956—61 Expenditure on Centrally Sponsored Schemes State Plan Schemes.
Finance (Planning and Development) Department, Madras State